Circadian rhythm, glucose metabolism and diabetic complications: the role of glucokinase and the enlightenment on future treatment - Zhang, Zhijun; Wang, Shuo; Gao, Ling (Frontiers in Physiology, 2025)
The circadian clock, an innate timing mechanism, governs a variety of physiological activities by producing near-24-h cycles in gene expression. These cycles are reflected in patterns of metabolism and behavior. This system consists of two parts: one is the central clock located in the suprachiasmatic nucleus of the hypothalamus, and the other is the peripheral clock located in tissues throughout the body. Glucokinase, also termed hexokinase 4, is a member of the hexokinase family. It acts as a glucose sensor, plays a pivotal role in glucose homeostasis. Here, we review the role of circadian rhythm in glucose metabolism across various tissues, look into the molecular mechanism of circadian disruption involvement in glucose metabolism and diabetic complications, with a particular focus on the role of glucokinase. Finally, we propose potential strategies for effectively treating metabolic disorders and diabetic complications by modulating circadian rhythm glucokinase.